Value chain analysis of non-timber forest products in Baglung district, Nepal - Paudel, A; Subedi, BP; Gyawali, S; Thapa, GK; Sharma, MB (Banko Janakari, 2010)
This study was carried out in five Village Development Committees of Baglung district, Nepal. The main objective was to assess the constraints and opportunities to run the non-timber forest products based enterprises, and to design business solutions to make their value chains more efficient and competitive with the best utilization of the available resources. Primary data were collected through group discussions, key informants interview, informal meetings and direct observations, using open-ended questionnaires and checklists. Similarly, secondary data were gathered from reports and records of community forest user groups, District Forest Office and other organizations. The data were analyzed using qualitative and quantitative tools. The identified major constraints concerning the selected value chains are: absence of detailed resource inventory; inadequate knowledge and skills with local people about modern technology and product quality parameters, local resource management policy and sustainable resource harvesting; insufficient finance with local processors; lack of sufficient information about market; and poor infrastructure development. In addition, the study also identified a number of opportunities such as the resource potential and monetary benefits to the local people; financial access through community forest user groups' fund and financial institutions; growing market demand for quality products; involvement of service providers in forest resource management; and supportive policy for employment generation from locally available natural resources. This paper has suggested some business solutions for the effective value chain of selected products. Key words: Business solution; constraints; non-timber forest products; opportunities; value chain DOI: 10.3126/banko.v19i2.2983 Banko Janakari, Vol. 19, No.2 2009 pp.33-41